Pengaruh Substrat yang Berbeda Terhadap Pertumbuhan dan Kelangsungan Hidup Kerang Abalon (Haliotis squamata) - Zain, Yusrina Ghina; Junaidi, Muhammad; Mulyani, Laily Fitriani (Universitas Teuku Umar, 2023)
The development of abalone cultivation technology in Indonesia is relatively slow because there are several obstacles experienced such as limited experts and technology for abalone hatchery. Abalone cultivation in the sea has various obstacles such as strong current, high waves and others. This requires environmental adjustment. One of them is the substrate as a place for the abalone to attach. The purpose of this study was to determine the effect of different substrates on the growth and survival of abalone (Haliotis squamata). This study used an experimental method using a completely randomized design (CRD) with 4 treatments and 3 repetitions. The treantmen used is the difference in substrate, namely roof tiles, pipes, zinc plastic and bamboo. The results showed that the average absolute length growth was 0,20-0,77 mm, the absolute weight ranged from 0,82-1,06 g and the survival rate was 43,66-77,00%. In conclusion the best treatment on the tile substrate.